The Influence of Chining-Up and Push-Up Training with Arm Length to Shooting Free Throw Result on Female Basketball Athletes at PGRI University of Palembang (Journal of Physical Education and Sports, 2018)
This study was aimed at analyzing (1) the difference of influence between chinning-up and push-up training to shooting free throw result on female basketball athletes in PGRI University of Palembang; (2) the difference of influence bettween athlete with long arm and athlete with short arm to shooting free throw result on female basketball athlete in PGRI University of Palembang; (3) the interaction between training method and arm length to shooting free throw result on female basketball athlete in PGRI University of Palembang. The research used quantitavive experimental method by using two factorial design. The treatments were arranged in such a way that each individual can be a simultaneous subject in two different factors in which each factor consists of several levels. Based on hypothesis testing result of the previous researches, resulted three analysis: (1) There is a difference of influence of chinning-up and push-up training method to shooting free throw result. (2) There is no difference of influence between the long arm category and the short arm category on female basketball athletes at PGRI University of Palembang. (3) There is an interaction effect between chinning-up training methods and arm length to shooting free throw result on female basketball athletes at PGRI University of Palembang.